2017
DOI: 10.17159/sajs.2017/20160244
|View full text |Cite
|
Sign up to set email alerts
|

Conservation implications of avian malaria exposure for African penguins during rehabilitation

Abstract: The African penguin (Spheniscus demersus) is the only penguin species that breeds on the African continent and it is currently classified as endangered. Its conservation is assisted by the Southern African Foundation for the Conservation of Coastal Birds (SANCCOB) which is a seabird rehabilitation facility based at the Rietvlei Wetland Reserve in Tableview, Cape Town. Despite the success of SANCCOB in rehabilitating diseased, injured or oiled penguins, significant mortalities have occurred at the facility as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In South Africa, research on avian haemosporidia has mostly focused on sea birds, which experience high infection rates as well as a huge diversity of avian haemosporidia (Okanga et al, 2014). A study at the Southern African Foundation for the Conservation of Coastal Birds (SANCCOB) found that African Penguins ( Spheniscus demersus ) presented for rehabilitation at the centre were highly susceptible to infection and usually acquired infection during rehabilitation (Botes et al, 2017). Strict vector control measures resulted in the decline of new malaria infections in these endangered birds.…”
Section: Introductionmentioning
confidence: 99%
“…In South Africa, research on avian haemosporidia has mostly focused on sea birds, which experience high infection rates as well as a huge diversity of avian haemosporidia (Okanga et al, 2014). A study at the Southern African Foundation for the Conservation of Coastal Birds (SANCCOB) found that African Penguins ( Spheniscus demersus ) presented for rehabilitation at the centre were highly susceptible to infection and usually acquired infection during rehabilitation (Botes et al, 2017). Strict vector control measures resulted in the decline of new malaria infections in these endangered birds.…”
Section: Introductionmentioning
confidence: 99%
“…Penguins participating in this study were housed with other rehabilitating penguins in pens according to their age groups and surrounded by insect protective nets. 11,27 Floors, pools, and feeding equipment were cleaned daily with F10 products (Health and Hygiene Ltd, Stormill, Randburg, South Africa). Over a period of 2 weeks all of the birds were fed whole fish and 10 of the animals received supportive feeding with EmerAid Piscivore (treatment group) and 11 animals (control group) were fed the hand-made fish formula; all birds were weighed daily before feeding.…”
Section: Methodsmentioning
confidence: 99%
“…In many other bird species, most individuals will have limited or no clinical signs, although clinical signs such as anaemia, necrosis of infected tissue, reduced reproductive success, reduced lifespan or a combination of these effects may impact some individuals (Asghar et al, 2015;Atkinson et al, 2008;Delhaye et al, 2018;Ishtiaq and Barve, 2018;Kilpatrick et al, 2006;Knowles et al, 2010;Valkiūnas, 2005). Healthy birds may be able to immunologically suppress the parasitaemia of these haemosporidians, resulting in chronic low levels of parasitaemia or a full recovery and immunity to further infection (Atkinson et al, 2008;Atkinson and Van Riper III, 1991;Botes et al, 2017;Rivero and Gandon, 2018;Valkiūnas, 2005).…”
Section: Introductionmentioning
confidence: 99%